(untitled) (Biological Sciences - PJSIR, 2000)
Pakistan refractory bricks industry is in infancy stage despite the fact that domestic demand of these bricks is growing fast and good quality refractory minerals are abundantly available in the country. Most of the refractory bricks requirements by local steel, glass, ceramics, oil refinery and other industries are being met through import. Important refractory minerals occurring in Pakistan include large deposits of chromite, magnesite, dolomite, bauxite, fire clay, kaolin, dunite and quartzite. This paper briefly reviews the quality and size of major refractory mineral deposits and various legal, financial, technical and other factors necessary for the development of refractory bricks industry in Pakistan.